Loeffler's syndrome following cutaneous larva migrans: An uncommon sequel - Indrashis Podder; Somodyuti Chandra; Ramesh Chandra Gharami (Wolters Kluwer Medknow Publications, 2016)
Cutaneous larva migrans (CLM) is characterized by the formation of distinctive, tortuous, and serpentine skin lesions occurring as a result of epidermal burrowing by certain helminthic larvae. Although this condition is usually uneventful, rarely it may result in patchy pulmonary infiltration with peripheral eosinophilia, also called Loeffler's syndrome. This association is fairly uncommon and is thus being reported.